Satisfying national and individual interests: impact evaluation of the KOICA master’s degree scholarship program - Kyuwon Kang; Junhyup Kim; Do Won Kwak (Journal of Contemporary East Asia Studies, 2024)
Precisely measuring the impact of official development assistance (ODA) programs is considered important, however, it has been a challenge for practitioners and politicians because of the lack of available data. While the Korea International Cooperation Agency (KOICA) Master’s Degree Scholarship (MDS) Program has run for many years, a formal system to assess its impact remains undeveloped. Thus, we evaluate the MDS program’s effect on participants’ individual outcomes (e.g. promotion, salary increase) and national outcomes (e.g. policymaking) using panel data. Furthermore, this study identifies traits of recipient countries and individuals that amplify the MDS program’s effects. To estimate the impact, we use a two-way fixed-effects framework. Specifically, we survey 80 participants from 36 countries on individual characteristics and outcomes across multiple periods before and after MDS participation. We find that the MDS program has a positive impact on both individual- and national-level outcomes. Specifically, the program shows a greater effect on salary increases for men in their 30s who hold a master’s degree in social sciences. Additionally, the effects are more pronounced for individuals from countries with a significant presence of Korean companies, a high Human Development Index (HDI), high GDP per capita, and strong governance scores. Furthermore, the implementation of policy benchmarking using Korean case studies tends to have a greater impact on women in their 30s with a master’s degree in natural sciences. These effects are also stronger for individuals from countries with a large Korean resident population and a low HDI.